PHARMACOKINETICS AND DYNAMICS OF MYCOPHENOLATE MOFETIL AFTER SINGE DOSE ORAL ADMINISTRATION IN JUVENILE DACHSHUNDS - Grobman, Megan (J Vet Pharmacol Ther, 2017)
Mycophenolate mofetil (MMF) is recommended as an alternative/complementary immunosuppressant. Pharmacokinetic and dynamic effects of MMF are unknown in young-aged dogs. We investigated the pharmacokinetics and pharmacodynamics of single oral dose MMF metabolite, mycophenolic acid (MPA), in healthy juvenile dogs purpose-bred for the tripeptidyl peptidase 1 gene (TPP1) mutation. The dogs were heterozygous for the mutation (non-affected carriers). Six dogs received 13mg/kg oral MMF and 2 placebo. Pharmacokinetic parameters derived from plasma MPA were evaluated. Whole blood mitogen-stimulated T cell proliferation was determined using a flow cytometric assay. Plasma MPA C(max) (mean ± Stdev, 9.33±7.04 μg/mL) occurred at <1 hr. The AUC(0-∞) (mean ± Stdev, 12.84±6.62 h* μg/mL), MRT(inf) (mean ± Stdev, 11.09±9.63 min), T1/2 (harmonic mean ± Pseudostdev 5.50±3.80 min), and k/d (mean ± Stdev, 0.002±0.001 1/min). Significant differences could not be detected between % inhibition of proliferating CD5+ T lymphocytes at any time point (P=0.380). No relationship was observed between MPA concentration and % inhibition of proliferating CD5+ T lymphocytes (R=0.148, P=0.324). Pharmacodynamics do not support the use of MMF in juvenile dogs at the administered dose based on existing therapeutic targets.